Evaluation of the Demographic Factors and Health Beliefs Associated with Screening Mammography in the Female Employees Aged 35 Years and More in the Schools of Medical Sciences in Abadan, Iran - Farkhonde Hayati; Rouhallah Rouhandeh (Mashhad University of Medical Sciences, 2018)
Introduction: Breast cancer is the most common cancer diagnosis among  women across the world. Successful breast cancer treatment depends on the early diagnosis of the disease. Mammography is a 'gold standard' screening method for breast cancer. The present study aimed to evaluate the demographic factors and health beliefs associated with screening mammography in the female employees aged 35 years and more in the state and Azad schools of medical sciences in Abadan, Iran. Methods: This descriptive study was conducted on 90 female employees in Abadan School of Medical Sciences and School of Nursing and Midwifery at Islamic Azad University of Abadan in 2017. Participants were selected via census sampling. Data collections tools were demographic and health beliefs questionnaires. Data analysis was performed in SPSS version 21 using Spearman's and Pearson's correlation-coefficient, and P-value of less than 0.05 was considered significant. Results: Significant associations were observed between the frequency of mammography and perceived sensitivity, as well as the education level of the spouse and perceived sensitivity (P=0.003). Mean perceived barriers in the subjects with a history of breast cancer in the first-degree relatives was higher compared to the perceived barriers in those with no history of breast cancer in their first-degree relatives. Moreover, mean perceived sensitivity was higher in the employees with a degree in medical sciences compared to those educated in humanities. Conclusion: According to the results, lack of knowledge on mammography was the main cause of the low rate of this screening method among the studied women. Therefore, it is recommended that codified educational programs be implemented in order to raise awareness regarding breast cancer screening.